Identification of a New Mutation (L46P) in the Human NOG Gene in an Italian Patient with Symphalangism Syndrome. - Athanasakis, E; Biarnés, X; Bonati, M T; Gasparini, P; Faletra, F (Mol Syndromol, 2012)
Proximal symphalangism (SYM1) is a joint morphogenesis disorder characterized by stapes ankylosis, proximal interphalangeal joint fusion, skeletal anomalies and conductive hearing loss. Noggin is a bone morphogenetic protein (BMP) antagonist essential for normal bone and joint development in humans and mice. Autosomal dominant mutations have been described in the NOG gene, encoding the noggin protein. We analyzed an Italian sporadic patient with SYM1 due to a novel NOG mutation (L46P) based on a c.137T>C transition. A different pathogenic mutation in the same codon (L46D) has been previously described in an in vivo chicken model. An in silico model shows a decreased binding affinity between noggin and BMP7 for both L46D and L46P compared to the wild type. Therefore, this codon should play an important role in BMP7 binding activity of the noggin protein and consequently to the joint morphogenesis.